Impact of Puberty in Girls on Prevalence of Primary Headache Disorder Among Female Schoolchildren in Kuwait - Alashqar, Abdelrahman; Shuaibi, Sameera; Ahmed, Samar Farouk; AlThufairi, Hawraa; Owayed, Shaikhah; AlHamdan, Fajer; Alroughani, Raed; Al-Hashel, Jasem Yousef (Frontiers in Neurology, 2020)
Background: The prevalence of primary headaches in the pediatric population is shaped by many factors, of which pubertal status may possibly play a substantial role. Epidemiological studies in the pediatric population in the gulf region remain scarce. Aims and objectives: To examine the impact of puberty on the prevalence of primary headache disorders among female schoolchildren in Kuwait. Methods: We conducted a cross-sectional study that included Kuwaiti primary and middle schoolgirls in randomly selected schools located in two governorates in Kuwait during the academic year 2018/2019. Prevalence of headache was assessed using the Headache-Attributed Restriction, Disability, Social Handicap and Impaired Participation (HARDSHIP) questionnaire for children and adolescents. Female students were asked about their menarchal status and whether they attained menarche before or after experiencing headaches. Results: The questionnaire was completed by 669 girls with a mean age of 11.44 ± 2.14 years. The 1-year prevalence of migraine headache disorder among girls was 23.62%, and the lifetime prevalence of any headache was 84.9%, whereas the 1-year prevalence of primary headache disorders was 47.98%. The mean age of girls with headaches was 11.44 ± 2.14 years. With respect to diagnostic criteria, migraine headache was the most frequently reported (23.62%), followed by tension-type headaches (20.93%), chronic headaches (2.99%), and probable medication-overuse headaches (0.45%). Postpubertal females were at significantly higher risk of having primary headaches compared to their prepubertal counterparts (64.26 vs. 34%; p < 0.0001). All types of primary headaches were more significantly prevalent among postpubertal girls compared to those who are prepubertal. Conclusion: Migraine headache is commonly reported among Kuwaiti schoolgirls. Postpubertal females are at higher risk of developing primary headaches compared to prepubertal females. Pubertal transition and female sex hormones may play a significant role in the pathophysiology of headaches, migraines in particular, and further research is therefore needed to investigate the underlying mechanisms.